Konseling Daring Pendukung Siswa Cerdas (KDPSC): A Preliminary Evaluation of iCBT Treatments for Indonesian Freshmen with Social Anxiety - Kurnia Yohana Yulianti; Yulia Wijayanti; Neila Ramdhani (Faculty of Psychology, Universitas Gadjah Mada, 2020)
During the transition period from adolescence to adulthood, individuals with high level of social anxiety may face challenges in their academics, social life, and career. The internet-based CBT (iCBT) module